Combating Academic Corruption: Quality Assurance and Accreditation - Eaton, Judith S. (International Higher Education, 2018)
The role of quality assurance and accrediting bodies in advancing academic integrity has long been clear. Increasingly, however, these bodies are also expected to focus on the challenging issue of academic corruption – practices such as plagiarism, fraudulent credentials, bribery – and how to end them. This article explores additional tools that quality assurance and accreditation may need to combat corruption, beyond advancing academic integrity.